2011
DOI: 10.1590/s0073-47212011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Dípteros ectoparasitas (Insecta, Diptera) em morcegos (Chiroptera, Mammalia) na Reserva Biológica das Perobas Paraná, Brasil

Abstract: Streblidae e Nycteribiidae são encontradas exclusivamente em associação com morcegos. Este trabalho teve como objetivo investigar a diversidade de insetos ectoparasitas encontrados em morcegos da Reserva Biológica das Perobas, Estado do Paraná, Brasil. O trabalho foi realizado nos meses de maio, junho e agosto de 2008 e fevereiro, março e abril de 2009. Para a captura dos morcegos, foram utilizadas 32 redes-de-neblina, totalizando esforço de captura de 43.520m².h. A coleta de ectoparasitas foi feita manualment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…per infested bat. The highest mean intensities were observed for P. longipes parasitising A. geoffroyi, which had not been recorded before in taxonomic inventories or in infestation analyses (Azevedo and Linardi, 2002;Komeno and Linhares, 1999;Bertola et al, 2005;Rui and Graciolli, 2005;Graciolli et al, 2006b;Graciolli and Aguiar, 2002;Dias et al, 2009;Silva and Ortêncio-Filho, 2011). The mean abundance calculated in the present study was higher than the values observed by Komeno and Linhares (1999) in the state of Minas Gerais (1.4) and by Bertola et al (2005) in the state of São Paulo (1.24).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…per infested bat. The highest mean intensities were observed for P. longipes parasitising A. geoffroyi, which had not been recorded before in taxonomic inventories or in infestation analyses (Azevedo and Linardi, 2002;Komeno and Linhares, 1999;Bertola et al, 2005;Rui and Graciolli, 2005;Graciolli et al, 2006b;Graciolli and Aguiar, 2002;Dias et al, 2009;Silva and Ortêncio-Filho, 2011). The mean abundance calculated in the present study was higher than the values observed by Komeno and Linhares (1999) in the state of Minas Gerais (1.4) and by Bertola et al (2005) in the state of São Paulo (1.24).…”
Section: Discussioncontrasting
confidence: 57%
“…Sampling effort is one of the criteria used to compare richness between localities, but in these studies on ectoparasitic flies it is remarkable that those differences depend more on other characteristics inherent to each physiognomy and on the host-species than on sampling effort. All species found in IZMA were already recorded for Brazil in different regions such as the Mid-Western (Graciolli and Aguiar, 2002;Graciolli et al, 2006a), southern (Rui and Graciolli, 2005;Graciolli and Bianconi, 2007;Silva and Ortêncio-Filho, 2011) and northeast of the country Dias et al, 2009). Among the nine streblid species recorded in the present study, just P. longipes was not even recorded in the Atlantic Forest of southeastern Brazil (Azevedo and Linardi, 2002;Bertola et al, 2005;Graciolli et al, 2006b).…”
Section: Discussionmentioning
confidence: 96%
“…The survey conducted at Chapada do Abanador presents a rich fauna of bat ectoparasites (14 bat fly species and nine mites) when compared to other works carried out in low Atlantic Forest areas in southern and southeastern Brazil , Rui and Graciolli, 2005, Camilotti et al 2010, Almeida et al 2011, Silva and Ortêncio Filho 2011. These studies recorded at least four bat fly species, with emphasis to the work by Almeida et al (2011) who sampled 10 bat fly species and 11 mites.…”
Section: Discussionmentioning
confidence: 99%
“…Made with Natural Earth. 1 Zarazúa‐Carbajal et al (); 2 ter Hofstede et al (); 3 Durán de la Ossa et al (); 4 Tarquino‐Carbonell et al (); 5 Santos et al (); 6 Soares et al (); 7 Barbier et al (); 8 Barbier et al (); 9 Santos et al (); 10 Soares et al (); 11 Bezerra et al (); 12 Bezerra and Bocchiglieri (); 13 Rios et al (); 14 Komeno and Linhares (); 15 Azevedo and Linardi (); 16 Barbier and Graciolli (); 17 Eriksson et al (); 18 Moras et al (); 19 Dornelles et al (); 20 Graciolli et al (); 21 França et al (); 22 Lourenço et al (); 23 Almeida et al (); 24 Bertola et al (); 25 Anderson and Ortêncio‐Filho (); 26 da Silva and Ortêncio Filho (), 27 Dornelles and Graciolli (), 28 Graciolli and Bianconi (), 29 Rui and Graciolli (), 30 Camilotti et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%